Augmented reality application for location finder guidance - Anatun Nadrah Rosman; Noor Azah Samsudin; Azizan Ismail; Muhammad Syariff Aripin; Shamsul Kamal Ahmad Khalid (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Finding directions to a specific location can be troublesome especially when we are not familiar with a new area. Conventionally, we may want to ask people around or possibly we use Global Positioning System (GPS) navigator. However, using GPS navigator may not be the best solution if the address is not entered accurately.  Therefore, this paper presents an augmented reality (AR) application for location finder guidance. Instead, a user is only required to scan the address indicated on a surface such as card or flyer using smart phone camera.The proposed application has utilized various components of AR technology including multiple image target, virtual button and markerless features. The development of the AR application follows phases of activities in Multimedia Mobile Content Development (MMCD) model. The proposed application is found to be very interactive and convenient in finding directions to specific location.